Analisis Penyebab Internal dan Eksternal dalam Fraudulent Financial Reporting: Studi Tinjauan Literatur - Fahrani, Andini Resa; Lestari, Adelia Sri; Putri, Nursela Rahma; Pasha, Nova Ayunda; Indrawati, Yuli; Halimah, Siti Nur (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: This research aims to analyze the internal and external causes that contribute to the occurrence of fraudulent financial reporting through a literature review, focusing on trends, developments, and under-explored areas.Methodology: This study analyzes 100 journals discussing the analysis of internal and external causes in fraudulent financial reporting from 2000 to 2024, sourced from reputable publishers. The research uses a systematic mapping study to identify, map, and categorize topics, methods, and source disciplines in fraudulent financial reporting research.Results: This study found that financial statement fraud is driven by a combination of internal factors (poor leadership, management dominance, lack of supervision, unrealistic targets, and excessive incentives) and external factors (financial pressures, rapid growth, and stock price pressure). The key finding is the interaction between these factors that triggers fraud.Conclusions: This study identifies internal and external factors, such as poor leadership, management dominance, and financial pressure, that trigger fraudulent financial reporting. It highlights the need for stronger governance and oversight to prevent FFR.Limitations: The study is based solely on a literature review of journals from 2000 to 2024, which may limit the scope of the research to the trends and findings presented in those publications.Contribution: The novelty of this study lies in highlighting the interaction between internal and external factors in fraudulent financial reporting and the need to strengthen regulatory oversight and corporate governance to prevent it.